2010
DOI: 10.1136/adc.2009.174417
|View full text |Cite|
|
Sign up to set email alerts
|

Survival of extremely preterm infants

Abstract: Draper et al 1 have highlighted the variation across Europe in outcomes of very preterm infants. Specifically, at 24–27 weeks' gestation, mortality as a percentage of infants alive at start of labour varied from 41.5% to 80.5%, and at <24 weeks' gestation from 0% to 9.7%. There is no mention, however, of the potential for variation within regions. We have recently audited the outcome for extremely preterm babies born alive within the city of Glasgow between 1 January 1998 and 31 December 2002

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The mortality of extremely preterm infants varies between 41.5% and 80.5%, and the risks of extreme prematurity are well described [8][9][10][11]. The cause of death for extremely low-birth-weight infants (501-1000 g) who die at less than 12 hours of age involves general immaturity of all organ systems, whereas infant deaths between 12 hours to 120 days and after 120 days are owing to respiratory distress syndrome and bronchopulmonary dysplasia, respectively [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality of extremely preterm infants varies between 41.5% and 80.5%, and the risks of extreme prematurity are well described [8][9][10][11]. The cause of death for extremely low-birth-weight infants (501-1000 g) who die at less than 12 hours of age involves general immaturity of all organ systems, whereas infant deaths between 12 hours to 120 days and after 120 days are owing to respiratory distress syndrome and bronchopulmonary dysplasia, respectively [12].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a large degree of survival variation in extreme prematurity is owing to the variable practices that occur in maternity and neonatal units [8]. Most deaths among less than 1000 g birth weight infants occur in the first 3 days of life [9].…”
Section: Discussionmentioning
confidence: 99%